The Evolving Urban Landscape in Nepal: Shifting Definitions Trends, and Spatial Patterns - Oli, Lal Bahadur (The Third Pole: Journal of Geography Education, 2025)
This article aims to analyse the changing urban landscape of Nepal, including trends, spatial patterns, and changing definitions. This study is based primarily on secondary data. Data were analysed using a descriptive approach. The study findings show that Nepal has experienced rapid urbanization over the last 70 years, with significant growth in urban areas and in the population. The definition of urban areas has changed over time, driven by major factors such as administrative reforms and migration, supported by changing administrative structures that classify urban areas as urban, sub-metropolitan, and metropolitan. However, many municipalities still retain their rural character. Similarly, the spatial patterns of urbanization in Nepal show regional disparities that are indicative of uneven development. Consequently, regional disparities and the expansion of peri-urban areas show the need for regional planning and integrated spatial strategies. In addition, government programs such as Smart Cities and Mega-Cities aim to use urbanization to boost economic growth and regional balance. Nepal is one of the least urbanized countries in the world, but it needs to implement effective policies and flexible management to ensure that urbanization leads to equitable growth, more jobs, and a better quality of life.